Influence of muscle volume on jumping performance in healthy male and female youth and young adults - Bchini, S.; Hammami, N.; Selmi, T.; Zalleg, D.; Bouassida, A. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Sex differences that appear throughout puberty have a substantial impact on the training process. It remains unclear what effect these sex differences should have on how training programs are planned and performed and what objectives should be established for boys and girls of different ages. This study aimed to investigate the relationship between vertical jump performance and muscle volume based on age and sex.